The role of cell cycle progression for the apoptosis of cancer cells induced by palladium(II)-saccharinate complexes of terpyridine. Issue 6 (15th March 2017) - Kacar, Omer; Cevatemre, Buse; Hatipoglu, Ibrahim; Arda, Nazli; Ulukaya, Engin; Yilmaz, Veysel T.; Acilan, Ceyda
Graphical abstract: Abstract: Objectives: Palladium complexes are potent and less toxic molecules in comparison to other metal based agents. Here, we characterized two palladium(II) saccharinate complexes with terpyridine for their cell cycle specificity. Materials and methods: Cells were arrested at G1, G1/S boundary or mitosis using mimosine, double-Thymidine block, aphidicolin, nocodazole or colcemid, and evaluated based on morphology and flow cytometry. Synchronized cells were treated with the Pd(II) complexes, and viability was measured via MTT assay. Results: While treatment of arrested cells with the Pd(II) complexes resulted in no significant change in cell death in HCT-116 and MDA-MB-231 cells, HeLa cells were more sensitive in S/G1. The main form of cell death was found to be apoptosis. Conclusions: Pd(II) complexes appear to be cell-cycle non-specific, while cell line dependent differences may be observed. Cells die through apoptosis regardless of the cell cycle stage, which makes these complexes more promising as anti-cancer agents.